A new variation of dual left anterior descending coronary artery. Issue 1 (July 2016) - Shizukuda, Yukitaka; Effat, Mohamed
Abstract: A 63-year-old male with past medical history of type II diabetes mellitus, hypertension, hyperlipidemia, stroke, and permanent pacemaker implant for poor chronotropic response to exercise underwent coronary computed tomography angiography (CCTA) for worsening atypical chest pain. The patient had normal myocardial perfusion by nuclear stress testing 3 months prior to this test. A rare variation of dual left anterior descending coronary artery (LAD) was identified by CCTA and subsequent coronary angiography confirmed a dual LAD and revealed no significant stenosis of the coronary arteries. Six types of dual LADs have been previously reported. However, this case showed a short LAD directly originating from the left coronary sinus and long LAD originating from the left main coronary artery. This configuration has not been reported previously in the literature to our knowledge. The short LAD main stem showed an intramyocardial course and provided septal perforators to the basal-mid interventricular septum (IVS) and right ventricular branches. The long LAD provided both diagonal branches and septal perforators to the distal IVS. CCTA in conjunction with coronary angiography played an essential role to characterize this anomaly and awareness of this anomaly merits reducing misinterpretation of coronary angiography for cardiology care providers. <Learning objective: Dual left anterior descending coronary artery (LAD) is an important coronary anomaly to be aware of by cardiology care providers to avoid misinterpretation of coronary angiography and surgical complications related to coronary interventions. We report a new variation of dual LAD which has not been reported previously and coronary computed tomography angiography helped to characterize this anomaly. Our case further expands anatomical variations of dual LADs.>